ANALISIS MENGENAI KEKUATAN HUKUM RISALAH RAPAT TERKAIT DENGAN PERJANJIAN OTENTIK DAN GUGATAN WANPRESTASI - Juan Antonius Piekarsa; Stanislaus Atalim (Jurnal Hukum Adigama, 2019)
An agreement is an event where a person promises to another person or where two people promise to do something. In an agreement, there are several legal aspects that become a condition for the agreement to be valid before the law. if one party does not implement one of the aspects of the agreement then that is known as a default. Breach of contract in a limited liability company that makes a contract with another limited liability company still has the possibility to be resolved in a minutes of meeting as in the event between PT Somit Trikonad and PT Timah Tbk. in this case we can see the force in effect of the minutes of the meeting in the agreement made by a limited liability company. Apart from the minutes of the meeting, it can also be seen that the valid force of the authentic deed in an agreement and the impact of the negligence of one party to the contract made.